Concerns about the social climate, finances, and COVID-19 risk on depression and anxiety: An analysis on U.S. young adults across two waves. (April 2022) - Liu, Cindy H.; Wong, Ga Tin Finneas; Hyun, Sunah; Hahm, Hyeouk "Chris"
Abstract: Concerns regarding contracting COVID-19 and finances may be risks to mental health during the COVID-19 pandemic. Social climate concerns may be another risk, given U.S. protests taking place during this period. We tested the hypothesis that concerns about COVID-19 risk, finances, and social climate would predict clinically significant levels of depression, anxiety, and comorbid depression and anxiety in young adults. A total of 782 U.S. young adults (18–30 years), initially recruited through convenience sampling (social media, email listservs), completed online surveys at Wave 1 (April–August 2020) and Wave 2 (September 2020–March 2021). The primary outcomes included scoring above the cut off for depressive (PHQ-8 ≥ 10) or anxiety symptoms (GAD ≥10). Approximately 41% reported depression and 47% reported anxiety at Wave 1; rates did not differ at Wave 2. Individuals with greater financial concerns were 14% more likely to score high on depressive symptoms; those with COVID-19 risk concerns and social climate concerns were 21% and 54% more likely, respectively, to score high on generalized anxiety. Those with social climate and financial concerns were 52% and 15% more likely, respectively, to score high on comorbid depressive and anxiety symptoms. Analyses controlled for Wave 1 symptoms. We provide evidence highlighting the roles of social climate and COVID-19 risk concerns on anxiety, and financial concerns on depression in young adults. Public health campaigns should acknowledge broader societal issues that have taken place as a source of mental health distress, beyond those driven by the pandemic (e.g., isolation and lockdowns).